Slow magnetic relaxation in high-coordinate Co(ii) and Fe(ii) compounds bearing neutral tetradentate ligands. Issue 42 (12th October 2021) - Peng, Min; Wu, Xiao-Fan; Wang, Li-Xin; Chen, Si-Huai; Xiang, Jing; Jin, Xin-Xin; Yiu, Shek-Man; Wang, Bing-Wu; Gao, Song; Lau, Tai-Chu
Abstract : 7-coordinate Co(ii ) compound has a very large positive D value (56.2 cm −1 ) with an effective spin-reversal barrier of U eff = 100 K (71.4 cm −1 ). In contrast, the 8-coordinate Fe(ii ) compound exhibits uniaxial magnetic anisotropy. Abstract : The first-row transition metal compounds, [M II (L 1 )2 ](ClO4 )2 (M = Ni (1 ); Co (2 )), have been prepared by treatment of a neutral tetradentate ligand (L 1 = N 2, N 9 -dibutyl-1, 10-phenanthroline-2, 9-dicarboxamide) with metal perchlorate salts in MeOH. Both compounds have been structurally characterized by X-ray crystallography and it was found that the coordination numbers are 6 and 7, respectively. The reaction of 6, 6′-bis(2- t butyl-tetrazol-5-yl)-2, 2′-bipyridine (L 2 ) with hydrated Fe II (ClO4 )2 afforded a 8-coordinate Fe(ii ) compound, [Fe II (L 2 )2 ](ClO4 )2 (3 ); however its reaction with hydrated Co II (ClO4 )2 resulted in 6-coordinate [Co II (L 2 )2 ](ClO4 )2 . It is interesting to observe field-induced slow magnetic relaxation in the 7-coordinate Co(ii ) compound 2 and 8-coordinate Fe(ii ) compound 3, which further supports the validity of designing high coordination number compounds as single-molecule magnets. Direct current magnetic studies demonstrate that 2 has a very large positive D value (56.2 cm −1 ) and a small E value (0.66 cm −1 ), indicating easy plane magnetic anisotropy. Consistent with the larger D value, an effective spin-reversal barrier of U eff = 100 K (71.4 cm −1 ) is obtained, which is the highest value reported for 7-coordinate Co(ii ) complexes with a pentagonal bipyramidal geometry. In contrast, 8-coordinate Fe(ii ) compound 3 exhibits uniaxial magnetic anisotropy.